2014
DOI: 10.1111/epp.12122
|View full text |Cite
|
Sign up to set email alerts
|

New distribution record of the invasive bronze bug Thaumastocoris peregrinus Carpintero and Dellapé (Heteroptera, Thaumastocoridae) in Italy

Abstract: The presence of the bronze bug Thaumastocoris peregrinus Carpintero and Dellapé (Heteroptera; Thaumastocoridae), a serious invasive pest of Eucalyptus (Myrtaceae) plantations, was recently reported for the first time in Europe in the Italian region of Latium. This study provides information on its occurrence in Sicily from Eucalyptus camaldulensis Dehnh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…P. bliteus parasitization is the main factor negatively influencing (=lowering) G. brimblecombei infestation; this result, together with the accidental and contemporaneous introduction of the psyllid and its parasitoid (CALECA et al, 2011a), could explain the absence of high damage level on eucalypts in Sicily, confirming results achieved by MARGIOTTA et al (2017) which state that P. bliteus parasitization causes a 64% reduction of the host population. In this context, it is to further investigate the influence that a strong attack of the invasive bronze bug Thaumastocoris peregrinus Carpintero & Dellapé (Hete roptera, Thaumastocoridae) can have against both the host and the parasitoid (SUMA et al, 2014(SUMA et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. bliteus parasitization is the main factor negatively influencing (=lowering) G. brimblecombei infestation; this result, together with the accidental and contemporaneous introduction of the psyllid and its parasitoid (CALECA et al, 2011a), could explain the absence of high damage level on eucalypts in Sicily, confirming results achieved by MARGIOTTA et al (2017) which state that P. bliteus parasitization causes a 64% reduction of the host population. In this context, it is to further investigate the influence that a strong attack of the invasive bronze bug Thaumastocoris peregrinus Carpintero & Dellapé (Hete roptera, Thaumastocoridae) can have against both the host and the parasitoid (SUMA et al, 2014(SUMA et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The arrival of P. bliteus in Italy (Sicily: CALECA et al, 2011a; Italian peninsula: LAUDONIA et al, 2014) is due to an accidental introduction, probably together with its host, as also happened in New Zealand, Brazil, Spain, Morocco, Greece, Tunisia, Portugal and Turkey (WITHERS, 2001;BERTI-FILHO et al, 2003;BERRY, 2007;PEREZ-OTERO et al, 2011;BAMI, 2011;BELLA and RAPISARDA, 2013;BELLA, 2014;DHAHRI et al, 2014;KARACA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between insects and their host plants are very interesting, especially if the plants are not native to the territory where the relationship is established (Bella 2008(Bella , 2013aSuma et al 2014 Denticera divisella has been considered as a possible agent for the biological control of the weed Euphorbia esula L. that, accidentally introduced in the 1800s in North America, spread widely and has been reported among the 'invasive alien weed species' by the United States Department of Agriculture. Preliminary laboratory tests have shown, however, that the moth larvae also feed on some ornamental euphorbia, and therefore D. divisella has not been included in the biological control program for this target species (Cristofaro et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The bronze bug is now widespread in many other areas: Africa (2003) (Zimbabwe, South Africa) (JACOBS and NESER, 2005; GILIOMEE, 2011), South America (2005) (Uruguay, Paraguay, Brazil, Chile, Argentina) (CARPINTERO and DELLAPÉ, 2006;NOACK and COVIELLA, 2006;MARTÍNEZ and BIANCHI, 2010;WILCKEN et al, 2010;IDE et al, 2011;SOLIMAN et al, 2012), Europe (2011), and recently the Middle East (2014) and New Zealand (SOPOW et al, 2012). The first report in Europe was recorded in Italy (2011) in the Lazio region (LAUDONIA and SASSO, 2012), followed by Portugal in 2012 (GARCIA et al, 2013), Sicily in 2014 (SUMA et al, 2014) and Sardinia in 2015 (DEIANA et al, 2018), where the first record was reported in the south of the island on E. camaldulensis.…”
Section: The Bronze Bugmentioning
confidence: 99%